If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x+3)=5(x+2/7)
We simplify the equation to the form, which is simple to understand
2(x+3)=5(x+2/7)
Reorder the terms in parentheses
+(+2x+6)=5*(x + 0.28571428571429)
Remove unnecessary parentheses
+2x+6=+5+*(+x + 0.28571428571429+)
Reorder the terms in parentheses
+2x+6=+(+5x+1.4285714285714)
Remove unnecessary parentheses
+2x+6=+5x+1.4285714285714
We move all terms containing x to the left and all other terms to the right.
+2x-5x=+1.4285714285714-6
We simplify left and right side of the equation.
-3x=-4.5714285714286
We divide both sides of the equation by -3 to get x.
x=1.5238095238095
| (3w-2)+55=180 | | 2(x+1)+5=7+2x | | 2x+14=2x-16 | | 2x+14=-7x-16 | | 4d+24=88 | | 0.5(4x-9)=2x+7 | | 6(x+7)=6(x+12) | | 155h=30 | | 9(a+7)=14a+23 | | 3x-7+9-x=x+12 | | 36x^2+11x=12 | | 3-3=4(3)-12 | | .5(4X-8)=2X+8 | | 4x+6=6(x+1)+2x | | -10x+12x=6 | | y=-0.5x^2+140 | | -(n-5)=-4n+26 | | 54x^2-2=3x | | 6(7x+8)=48 | | 6j-8=34 | | 0=5.8+-9.8t | | x+38=5x+10 | | (-5)(4-5x)=7x-3(3x-9) | | -8[-x-6]+2=-22 | | 4(c+12)=c+18 | | -42-5b=-6(5b-2)-2b | | 13x+41=4x+15 | | 3x+12y=117 | | 5u-16=54 | | x=240-2y | | 2[n+10]+3=11 | | 3-x=4x-12 |